The loss-of-function of AtNATA2 enhances AtADC2-dependent putrescine biosynthesis and priming, improving growth and salinity tolerance in Arabidopsis - Jasso-Robles, Francisco Ignacio; Aucique-Perez, Carlos Eduardo; Zeljković, Sanja Ćavar; Saiz-Fernández, Iñigo; Klimeš, Pavel; De Diego, Nuria (Physiologia plantarum, 2024)
Putrescine (Put) is a promising small molecule-based biostimulant to enhance plant growth and resilience, though its mode of action remains unclear. This study investigated the Put priming effect on Arabidopsis mutant lines (Atadc1, Atadc2, Atnata1, and Atnata2) under control conditions and salinity to understand its role in regulating plant growth. The Atadc2 mutant, characterized by reduced endogenous Put levels, showed insensitivity to Put priming without growth enhancement, which was linked to significant imbalances in nitrogen metabolism, including a high Gln/Glu ratio. Contrarily, the Atnata2 mutant exhibited significant growth improvement and upregulated AtADC2 expression, particularly under Put priming, highlighting these genes' involvement in regulating plant development. Put priming enhanced plant growth by inducing the accumulation of specific polyamines (free, acetylated, conjugated, or bound form) and improving light-harvesting efficiency, particularly in the Atnata2 line. Our findings suggest that AtNATA2 may negatively regulate Put synthesis and accumulation via AtADC2 in the chloroplast, impacting light harvesting in photosystem II (PSII). Furthermore, the Atadc2 mutant line exhibited upregulated AtADC1 but reduced AcPut levels, pointing to a cross-regulation among these genes. The regulation by AtNATA2 on AtADC2 and AtADC2 on AtADC1 could be crucial for plant growth and overall stress tolerance by interacting with polyamine catabolism, which shapes the plant metabolic profile under different growth conditions. Understanding the regulatory mechanisms involving crosstalk between AtADC and AtNATA genes in polyamine metabolism and the connection with certain SMBBs like Put can lead to more effective agricultural practices, improving plant growth, nitrogen uptake, and resilience under challenging conditions.
Keywords: putrescin; Photosystem II Protein Complex; Arabidopsis; proteiny huseníčku; polyaminy; fotosystém II (proteinový komplex); Salt Tolerance; tolerance k soli; Loss of Function Mutation; Putrescine; Arabidopsis Proteins; Polyamines; mutace ztráty funkce; regulace genové exprese u rostlin; Gene Expression Regulation, Plant